The development of enzyme-linked immunosorbent assays to detect potato virus Y and potato leaf roll virus using recombinant viral coat proteins as antigens - Matzopoulos, Mark (Stellenbosch : University of Stellenbosch, 2011)
Thesis (MSc)--University of Stellenbosch, 2005.